(untitled) (Global Journal of Management and Business Research, 2019)
Manpower Planning is an obvious and extremely critical function of some inter-related explicit operational and functional Factors of an organization s overall people resource attributes methodology and strategic initiatives In India the employment competence functions manpower planning and execution decisions models and implications of them at the micro and macro environments of the organizations have still some role to play Manpower planning models have been evolved to cater situational necessities of the workforce and at the same time leaves the scope of in-depth review and analysis of their limitations and corrective aspects The reflections of utility analysis and allied assessment of costbenefits also clarify the usage of alternative utility functions through systematic and logical approaches The in-depth analysis and managerial perceptions on the analysis of outcomes have Significant roles in successful implementation of any manpower planning models in any given strategic corporate environment